2021
DOI: 10.3390/microorganisms9102162
|View full text |Cite
|
Sign up to set email alerts
|

Enrofloxacin Alters Fecal Microbiota and Resistome Irrespective of Its Dose in Calves

Abstract: Enrofloxacin is a fluoroquinolone drug used to prevent and control bovine respiratory disease (BRD) complex in multiple or single doses, ranging from 7.5 to 12.5 mg/kg body weight. Here, we examined the effects of high and low doses of a single subcutaneously injected enrofloxacin on gut microbiota and resistome in calves. Thirty-five calves sourced for this study were divided into five groups: control (n =7), two low dose groups (n = 14, 7.5 mg/kg), and two high dose groups (n = 14, 12.5 mg/kg). One group in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Subcutaneously administered enrofloxacin to calves achieved the intestinal concentration that could decrease intestinal bacteria 42 . Further, our metagenomic studies 21 , 22 have revealed that the fecal microbial diversity has been significantly changed in calves; some bacterial taxa responded differently to the low and high enrofloxacin doses. The fecal resistome profiles have been affected remarkably in FQs administered groups compared to the control groups 21 , 22 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Subcutaneously administered enrofloxacin to calves achieved the intestinal concentration that could decrease intestinal bacteria 42 . Further, our metagenomic studies 21 , 22 have revealed that the fecal microbial diversity has been significantly changed in calves; some bacterial taxa responded differently to the low and high enrofloxacin doses. The fecal resistome profiles have been affected remarkably in FQs administered groups compared to the control groups 21 , 22 .…”
Section: Discussionmentioning
confidence: 86%
“…In this study, there were four groups of calves: low-dose control, low-dose BRD, high-dose control, and high-dose BRD. The animal study was detailed in our recent publication 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Both experimental and observational studies indicated that antibiotic use and thus, the resultant selection pressure is an important factor driving the emergence and persistence of ARB and their resistance genes [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Mastitis is the most frequent disease of dairy cattle; and ceftiofur is the most commonly used antimicrobial drug used to manage it [ 5 , 68 ].…”
Section: Use Of Beta-lactam Antibiotics In the Usa Dairy Cattle Farmsmentioning
confidence: 99%
“…The importance of the gut microbiota has led to an increase in the number of studies investigating the role of bacterial communities on the health and disease of neonatal calves. The impact of different intervention and management practices (eg, antimicrobial drugs, colostrum, or probiotic administration) on the gut microbiota has also been frequently investigated 1‐5 . Most of these studies explore the variation on fecal characteristics and microbiota over time by collecting samples on a weekly basis 2,6‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of different intervention and management practices (eg, antimicrobial drugs, colostrum, or probiotic administration) on the gut microbiota has also been frequently investigated. 1 , 2 , 3 , 4 , 5 Most of these studies explore the variation on fecal characteristics and microbiota over time by collecting samples on a weekly basis. 2 , 6 , 7 , 8 During such weekly visits, researchers collect feces from all animals enrolled in the study.…”
Section: Introductionmentioning
confidence: 99%